2019
DOI: 10.1074/jbc.ra119.009468
|View full text |Cite
|
Sign up to set email alerts
|

The pseudosubstrate inhibitor Acm1 inhibits the anaphase-promoting complex/cyclosome by combining high-affinity activator binding with disruption of Doc1/Apc10 function

Abstract: The anaphase-promoting complex/cyclosome (APC/C) is a large, multisubunit ubiquitin ligase involved in regulation of cell division. APC/C substrate specificity arises from binding of short degron motifs in its substrates to transient activator subunits, Cdc20 and Cdh1. The destruction box (D-box) is the most common APC/C degron and plays a crucial role in substrate degradation by linking the activator to the Doc1/Apc10 subunit of core APC/C to stabilize the active holoenzyme and promote processive ubiquitylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…APC/C substrates interact with the activator WD40 domain via short linear sequence motifs called degrons, of which the D box, KEN box, and ABBA motif are the most common 18,2229 . Cooperative binding of multiple degron sequences to the activator subunit provides the affinity required for efficient and processive ubiquitylation, and the affinity of degron binding is likely to influence the timing of degradation in vivo 26,30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…APC/C substrates interact with the activator WD40 domain via short linear sequence motifs called degrons, of which the D box, KEN box, and ABBA motif are the most common 18,2229 . Cooperative binding of multiple degron sequences to the activator subunit provides the affinity required for efficient and processive ubiquitylation, and the affinity of degron binding is likely to influence the timing of degradation in vivo 26,30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the A-box with a panel of D-boxes showed that it docks with an affinity within the range of known D-boxes, although with reduced affinity compared to more canonical D-boxes (Supplementary Figure S4). We note that in silico docking to FZR1 alone ignores any contacts made between substrate and APC10 that probably contribute to the affinity of substrate for the D-box binding pocket (Qin et al 2019) and therefore we may have underestimated the likely preference of Q 45 RVL for the DBR.…”
Section: Resultsmentioning
confidence: 99%
“…Key factors include the specificity and affinity of individual degrons for the activator and Apc10, as well as the presence of multiple degrons on a substrate. Numerous other factors are also likely to be important, such as the number and positioning of lysines for modification, the distance between degrons, and the orientation of the D box at its bivalent binding site 7,16,18,40 .…”
Section: Discussionmentioning
confidence: 99%
“…The Nterminal RxxL segment interacts with an acidic patch and aliphatic pocket on the WD40 domain of the activator 10 . The C-terminal residues of the D box interact with the Apc10 subunit [16][17][18] . As a result, the D box helps anchor the activator to the APC/C 19,20 .…”
Section: Introductionmentioning
confidence: 99%